Research on the Theoretical Foundation, Connotation Dimension and Construction Path of Chemistry Curriculum Ideological and Political Education - Tian, Xiong; Liao, Qingling (Education Insights, 2026)
Driven by the intensifying mission to foster virtue through education within the Chinese higher education landscape, the strategic integration of value-based guidance into academic curricula has emerged as the primary vehicle for achieving a comprehensive and holistic instructional environment. Chemistry, as a discipline, is uniquely defined by its combination of rigorous scientific theory and extensive practical utility. Consequently, embedding ideological elements into chemistry courses is not merely a critical step in enhancing the caliber of professional training; it is also instrumental in nurturing students’ logical reasoning, ethical standards, and civic accountability. By synthesizing domestic and international scholarly progress from the last five years, this study dissects the multi-layered theoretical framework that supports value-integrated chemistry education. It provides a detailed analysis of six essential pillars—including scientific integrity, patriotism, and cultural pride—and distills an operational model characterized by "six dimensions and four pillars" derived from current pedagogical practices. Furthermore, the paper addresses existing bottlenecks, such as undeveloped assessment tools and fragmented resource utilization, by proposing targeted optimization strategies. This research aims to offer a fresh theoretical benchmark for innovating and standardizing the practical implementation of ideological-political education in chemistry, ultimately laying a solid groundwork for preparing a new generation of chemical experts who possess both professional excellence and unwavering social convictions.